Antibacterial activity of four marine seaweeds collected from the coast of Gaza Strip, Palestine - Elnabris, K.J.; Elmanama, A.A.; Chihadeh, W.N. (Mesopotamian Journal of Marine Sciences, 2022)
Four commonly occurring marine seaweeds; Ulva lactuca, Enteromorpha compressa (Chlorophyta), Padina pavonica (Phaeophyta) and Jania rubens (Rhodophyta) were collected from the coast of Gaza strip, Palestine. Crude extracts were prepared using the solvent methanol and evaluated for antibacterial activity by well diffusion method against both Gram negative (Escherichia coli, Pseudomonas aeruginosa, Proteus vulgaris and Klebsiella pneumoniae) and Gram-positive bacteria (Staphylococcus aureus and Bacillus subtilis). The crude methanolic extract of U. lactuca inhibited the growth of all the test organisms except E. coli. Seaweed extract of E. compressa was found to be effective against two of the examined bacteria. Algae belonging to Chlorophyta showed higher antibacterial activity than other members of the algae tested in the present investigation. The methanol extracts of brown and red algae did not show any significant effect on the growth of tested bacteria. E. coli was resistant to all the extracts. Results of the present study confirmed the potential use of seaweed extracts as a source of antibacterial compounds.